Could a future "Grand Solar Minimum" like the Maunder Minimum stop global warming?. Issue 9 (13th May 2013) - Meehl, Gerald A.; Arblaster, Julie M.; Marsh, Daniel R.
<x xml:space="preserve">Abstract</x> [1] A future Maunder Minimum type grand solar minimum, with total solar irradiance reduced by 0.25% over a 50 year period from 2020 to 2070, is imposed in a future climate change scenario experiment (RCP4.5) using, for the first time, a global coupled climate model that includes ozone chemistry and resolved stratospheric dynamics (Whole Atmosphere Community Climate Model). This model has been shown to simulate two amplifying mechanisms that produce regional signals of decadal climate variability comparable to observations, and thus is considered a credible tool to simulate the Sun's effects on Earth's climate. After the initial decrease of solar radiation in 2020, globally averaged surface air temperature cools relative to the reference simulation by up to several tenths of a degree Centigrade. By the end of the grand solar minimum in 2070, the warming nearly catches up to the reference simulation. Thus, a future grand solar minimum could slow down but not stop global warming.